Review on Eggshell Waste in Tissue Engineering Application - Razak, Siti Aisyah; Mat Isa, Najah Anis Aqilah; Syed Abu Bakar, Sharifah Adzila (International Journal of Integrated Engineering, 2022)
Eggshell waste (EW) is an abundant waste from group of municipal solid waste that being ignored for a long time until it potential in various field being developed. High calcium content in EW make it one of the choice to be combined with other material for tissue engineering application. The aim of this article is to review EW from waste, EW reinforced biocomposite and it fabrication method and lastly current issue and future development. EW that contain high calcium carbonate (CaCO3) make it suitable for biomaterial application as it can be extract to become various type of calcium phosphate. Biocomposite from metal, ceramic and polymer being focused including it different type of fabrication due to suitability of processing method on different material. Current issue about the abundant waste had make future development of EW as one of the waste that have potential to be commercialize as source of biomaterial source.